Spiritual Habituation and Character Development in Elementary Education: A Qualitative Study from Indonesia - Jumsir Jumsir; Dadang Sumarna; Rosmiati Ramli; Sumadin Sumadin; Muhammad Nur Maallah (CV. Gerasi Insan Nusantara, 2026)
The growing concern over moral decline and weakening spiritual values among young learners has highlighted the need for effective approaches to character and spiritual development in schools. Although previous studies have emphasized the importance of character education, limited research has explored how habituation-based spiritual education contributes to students’ spiritual character formation in elementary school settings. This study investigates the implementation of spiritual education through habituation practices and examines its impact on students’ spiritual attitudes and behaviors at SD Negeri Kecil Banua, Indonesia. A qualitative descriptive design was employed using theological, pedagogical, and psychological perspectives. Data were collected through observations, semi-structured interviews, and documentation involving the principal, Islamic Religious Education teachers, and students. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while trustworthiness was ensured through triangulation techniques. The findings reveal that spiritual education is effectively implemented through structured habituation activities, including daily prayers, congregational Dhuha prayer, Qur’anic recitation, greetings, and the cultivation of honesty, discipline, and respect. These practices have contributed significantly to the development of students’ spiritual awareness, worship discipline, moral responsibility, and positive social behavior. The study also identifies teacher role-modeling, supportive school policies, and a conducive religious environment as key supporting factors, whereas limited instructional time and inconsistent reinforcement outside school remain major challenges. The findings suggest that habituation-based spiritual education serves as an effective strategy for strengthening students’ spiritual character and fostering holistic development in elementary education. The study contributes to the growing literature on spiritual pedagogy and character education in primary school contexts.